COL18A1 is a candidate eye iridocorneal angle-closure gene in humans. (11th July 2018) - Suri, Fatemeh; Yazdani, Shahin; Chapi, Marjan; Safari, Iman; Rasooli, Paniz; Daftarian, Narsis; Jafarinasab, Mohammad Reza; Ghasemi Firouzabadi, Saghar; Alehabib, Elham; Darvish, Hossein; Klotzle, Brandy; Fan, Jian-Bing; et al.
Abstract: Primary angle-closure glaucoma (PACG) is a common form of glaucoma in the Far East. Its defining feature is iridocorneal angle closure. In addition to PACG, indications of angle closure are included in the diagnostic criteria of related conditions primary angle-closure suspect (PACS) and primary angle closure (PAC). To the best of our knowledge, a causative gene for iridocorneal angle closure in humans has not been identified. This study aimed to identify the genetic cause of iridocorneal angle closure in a pedigree with at least 10 individuals diagnosed with PACS, PAC or PACG. Results of linkage analysis, segregation analysis of 44 novel variations, whole exome sequencing of 10 individuals, screenings of controls and bioinformatics predictions identified a mutation in COL18A1 that encodes collagen type XVIII as the most likely cause of angle closure in the pedigree. The role of COL18A1 in the etiology of Knobloch syndrome (KS) that is consistently accompanied by optic anomalies, available functional data on the encoded protein and the recognized role of collagens and the extracellular matrix in glaucoma pathogenesis supported the proposed role of the COL18A1 mutation in the pedigree. Subsequent identification of other COL18A1 mutations in PACS affected individuals of two unrelated families further supported that COL18A1 may affect angle closure. These PACS individuals were parents and grandparents of KS-affected children. In conclusion, a gene that affects angle closure in humans, a critical feature of PACG, has been identified. The findings also reinforce the importance of collagens in eye features and functions.